Pengaruh Kualitas dalam Fitur Produk di Bank Syariah Indonesia (BSI) Terhadap Kepuasan Mahasiswa UIN SMH Banten - Malda Komala; Melianah Anggreani; Nurbaeti Nurbaeti; Henny Saraswati; Wahyu Hidayat (International Forum of Researchers and Lecturers, 2023)
The purpose of this study was to determine the effect of the product quality characteristics of Bank BSI on student satisfaction at UIN SMH Banten. This study uses a quantitative approach and survey techniques. A total of 33 students from UIN SMH Banten received the question sheets. The analysis of the collected data was carried out using descriptive and inferential statistical methods. Product Features Bank Syariah Indonesia's digital product, BSI Mobile aims to facilitate customer transactions and provide information to customers through the features offered. The second most important factor is feature development because product features are undeniable product benefits and characteristics that customers can directly use. Simple linear regression tests, t-tests (individually), F-tests, and validity tests were used to demonstrate and analyze. These results indicate that since the corrected elemental overall correlation is greater than 0.3, the product characteristics related to student satisfaction have been accepted as valid. The BSI Mobile-Product Mark is known to have a significance value (Sig.) of 0.000, which indicates that the significance value of the BSI Mobile-Product Brand is less than 0.05 (= 5%). Therefore, this shows that H0 will be rejected and H2 will be accepted. The main result of this study is that there is a significant relationship between student satisfaction at UIN SMH Banten with product features of BSI Mobile.